Effect of pyrrole implants synthesized by different methods on spinal cord injuries of rats - Álvarez- Mejía, L (Revista Mexicana de Ingenieria Biomedica, 2015)
Polypyrrole (PPy) and polypyrrole/polyethylene glycol (PPy/PEG) implants synthesized by chemical, electrochemical, and plasma polymerization methods were implanted into the injured spinal cord of rats to determine their effect on motor function recovery. Before implantation, the materials were characterized by infrared (IR) spectroscopy. An experimental model of traumatic spinal cord injury (TSCI) by the complete transaction at thoracic level 9, in rats, was used. The polymer implants were inserted immediately after transaction. Motor function recovery was evaluated once a week during 5 weeks using the Basso, Beattie and Bresnahan (BBB) motor scale. Histological evaluation was done at the end of the recovery evaluation period using hematoxylin/eosin stain. Results showed that animals implanted with polymers synthesized by plasma had a better integration into the nerve tissue, less inflammatory response and a better functional recovery than animals implanted with polymers synthesized by chemical or electrochemical methods.